Healthcare systems in Poland and Germany: historical outline and comparative analysis - Szulik, Janusz; Świtalski, Jakub; Wnuk, Katarzyna; Wrześniewska-Wal, Iwona; Opolski, Janusz; Augustynowicz, Anna (Medical Studies/Studia Medyczne, 2026)
In public debate in Poland, the experiences of other countries are often considered in an effort to optimize the healthcare system. One of the countries frequently mentioned in this context is Germany. The purpose of this article is to compare the German and Polish healthcare systems with special attention being paid to indicators related to the functioning of the healthcare system as well as indicators of the population health status. Presentation of selected indicators was made, among others, on the basis of data available from the Organization for Economic Co-operation and Development (OECD). Conclusions can be drawn regarding clear differences in the organization of the healthcare systems in Poland and Germany. The vast majority of health status indicators, as well as indicators related to the functioning of the healthcare system, look better in Germany than in Poland.